2009
DOI: 10.1242/jeb.034462
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the effect of prey properties on feeding kinematics in two species of lizards

Abstract: SUMMARYStudies of the functional morphology of feeding have typically not included an analysis of the potential for the kinematics of the gape cycle to vary based on the material properties of the prey item being consumed. Variation in prey properties is expected not only to reveal variation in feeding function, but allows testing of the functional role of the phases of the gape cycle. The jaw kinematics of two species of lizards are analyzed when feeding trials are conducted using quantitative control of prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…SC duration has been shown to vary with food hardness in both lizards and mammals (Herrel et al, 1996;Hiiemae et al, 1995;Hiiemae et al, 1996;Metzger, 2009;Schaerlaeken et al, 2008;Thexton and Hiiemae, 1997;Yamada and Haraguchi, 1995;Yamada and Yamamura, 1996) but it is not known to what extent this variation in SC duration impacts variation in overall gape cycle duration. Our hypothesis, that the lower cycle duration variance in mammals is attributable to feed-forward, rate-modulation of bite force during SC, predicts that variance in SC duration significantly impacts variance in overall cycle duration in both mammals and lizards and that SC duration is less variable in mammals than in lizards.…”
Section: Slow-closementioning
confidence: 99%
See 1 more Smart Citation
“…SC duration has been shown to vary with food hardness in both lizards and mammals (Herrel et al, 1996;Hiiemae et al, 1995;Hiiemae et al, 1996;Metzger, 2009;Schaerlaeken et al, 2008;Thexton and Hiiemae, 1997;Yamada and Haraguchi, 1995;Yamada and Yamamura, 1996) but it is not known to what extent this variation in SC duration impacts variation in overall gape cycle duration. Our hypothesis, that the lower cycle duration variance in mammals is attributable to feed-forward, rate-modulation of bite force during SC, predicts that variance in SC duration significantly impacts variance in overall cycle duration in both mammals and lizards and that SC duration is less variable in mammals than in lizards.…”
Section: Slow-closementioning
confidence: 99%
“…However, our data analysis revealed that lepidosaurs and primates do not differ in SC variance. SO is the most variable phase in mammals (Schwartz et al, 1989;Thexton et al, 1980;Yamada and Yamamura, 1996) and lizards (Delheusy and Bels, 1992;Herrel et al, 1996;Metzger, 2009) suggesting that SO duration variance might contribute significantly to total cycle duration variance in both groups. We compared variation in SO in lepidosaurs and mammals and estimated the relative importance of SO variance in driving cycle duration variance.…”
Section: Slow Openmentioning
confidence: 99%
“…Such variability in feeding movements has been documented extensively in squamate lizards during both the capture and intra-oral transport and processing of food (e.g. Bels and Baltus, 1988;Herrel et al, 1996;Herrel et al, 1999;Smith et al, 1999;Schaerlaeken et al, 2007;Schaerlaeken et al, 2008;Sherbrooke and Schwenk, 2008;Metzger, 2009;Montuelle et al, 2010;Schaerlaeken et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bels and Baltus, 1988;Herrel et al, 1996;Delheusy and Bels, 1999;Herrel et al, 1999;Schaerlaeken et al, 2007;Schaerlaeken et al, 2008;Metzger, 2009;Montuelle et al, 2009b;Montuelle et al, 2010;Schaerlaeken et al, 2011). Regarding prey size (here represented by prey length), we expected that the larger the prey, the higher the cranio-cervical system would have to rise.…”
Section: Introductionmentioning
confidence: 99%
“…In lizards, true feeding specialists are rare. Indeed, most lizards feed on a wide variety of food items that often differ in their physical and behavioral characteristics (Greene, ; Schaerlaeken et al., , ; Metzger, ; Montuelle et al., ). If prey properties impose specific mechanical demands on the feeding system of the predator, then these will likely influence the efficiency of prey capture and transport (Meyers and Herrel, ).…”
mentioning
confidence: 99%